Effect of Weather and Environmental Conditions on the Performance Parameters of 3 Salient Photovoltaic at UTHM Johor - Anuwar, Eza Elhanis; Islam , Syed Zahurul (Evolution in Electrical and Electronic Engineering, 2022)
As is generally known, a multitude of production procedures are used to create PV panels today. Varying solar panel types react differently to environmental factors such as radiation, temperature, and wind speed. They also have different voltage and current values, spectrum responses, and temperature coefficients. However, the difficulty in this study is to examine the actual PV performance data to differentiate the information for the three main types of PV panels in order to determine the best panel. So, the purpose of this project is to review the three types of solar panel performance under real weather and environmental conditions and to identify the most suitable solar panel to be installed in UTHM. After installing all three solar panels, their performance parameters will be compared in order to choose which one is the most suitable to be installed in UTHM. The data will be collected every 15 minutes from 11:40 a.m. until 4:40 p.m and the experiment are only 5 hours. After the experiment has succeeded, the data collection from the memory card needs to transfer to Microsoft Excel to continue doing the analysis of this project. After the experiment was completed, data analysis was performed where for efficiency, monocrystalline recorded a better value while for performance ratio, polycrystalline had a better value. For OPE, thin films show a more stable graph than the others. However, for overall results, polycrystalline is the best panel compared to monocrystalline and thin film.